Análisis del perfil del consumidor financiero de la ciudad metropolitana de Iquitos y Tarapoto periodo 2022 - Villacorta Mallqui, Manuel Alejandro (2025)
The objective was to characterize and compare the financial consumer profile of Iquitos and Tarapoto, 2022. This study is basic, descriptive, quantitative, prospective with non-experimental design, comparative cross-sectional. The population includes 366,715 people aged 18 to 70, men and women, from rural and urban areas, with a sample of 382 selected proportionally in Iquitos and Tarapoto, using stratified random probabilistic sampling. A survey was applied with a 24-item questionnaire using an ordinal and nominal scale. The stability of the reliability index of the questionnaire with the test-retest method was 98%; Aiken's content validity index V is 1, p = 0.032. The financial consumer profile that most impacts decisions is behavioral in Iquitos (40%) and Tarapoto (42%), followed by the psychographic profile in Iquitos (30%) and Tarapoto (28%). The demographic aspects (20%-22%) and sociocultural aspects (8%-10%) in Iquitos and Tarapoto, respectively, are influential in the segmentation, but do not determine the final consumer election in both cities. However, it is evident that there are similarities in the psychographic and behavioral profile of the financial consumer between both cities, while the demographic and sociocultural profile shows differences. Tarapoto shows a lower frequency of financial consumer profile than Iquitos. In summary, there is a significant difference in the profiles of financial consumers between Iquitos and Tarapoto, period 2022 (p= 0.012).